SOCIAL AND ECONOMIC CONDITIONS OF WOMEN IN GUPTA PERIOD - Sangita Minz (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Since ancient times, women were being respected and honored in Hindu society. Women are the cornerstone of society. She could achieve self-development and upliftment as per her wish. The germination of a man’s personality lies in his mother’s number. That is his primary and first Shiva temple. The contribution made by them in the family and community as daughters, wives, brides and mothers has a very important and proud place. In religious scriptures, women are considered omnipotent and are considered a symbol of love, fame and wealth. Gradually its importance increased in the society that without it a single man was considered incomplete and incomplete. If mother is the nurturing ground of a man’s character then wife is the pillar of his development.